2022
DOI: 10.17113/ftb.60.02.22.7419
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Functional Potential of Carob Syrup Versus Date and Maple Syrup

Abstract: Research background. The carob tree (Ceratonia siliqua L.) is grown primarily for its seeds that are utilized in the production of the highly-prized locust bean gum. The material left after the separation of seeds, from the pods, is utilized in the production of a range of traditional products including carob syrup usually in cottage-type industries. The international market penetration of carob syrup is rather limited and, accordingly, scant information exists on their composition and phytochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The specific differentiation in Brix degrees is likely due to the final boiling time, which is also responsible for the final concentration degree of the product. The pH values of the carob syrups analyzed in this study ranged from 4.91 to 5.91 and are in agreement with similar studies that have found the pH value of carob syrup ranged from 4.3 to 5.4 [31]. Organic acids, as well as minerals contained in syrups, mainly account for their acidic pH.…”
Section: Carob Syrupsupporting
confidence: 92%
See 1 more Smart Citation
“…The specific differentiation in Brix degrees is likely due to the final boiling time, which is also responsible for the final concentration degree of the product. The pH values of the carob syrups analyzed in this study ranged from 4.91 to 5.91 and are in agreement with similar studies that have found the pH value of carob syrup ranged from 4.3 to 5.4 [31]. Organic acids, as well as minerals contained in syrups, mainly account for their acidic pH.…”
Section: Carob Syrupsupporting
confidence: 92%
“…The carob syrup used to prepare the carob beers had a total phenolic content of 911.4 ± 19 mg GAE/100 mL, antioxidant capacity expressed as 6464 ± 69.6 mg Fe 2+ /100 mL, and antiradical activity 2514 ± 45.3 TE/100 mL. Similar studies have determined a mean value of 729 ± 487 g GAE/100 g among 14 carob syrups [31] and 9.51-14.80 mg GAE/g among nine carob syrups from Cyprus and Greece [36]. The high concentration of polyphenols makes the carob syrups ideal as additives and capable of enriching foods and beverages with antioxidants.…”
Section: Total Phenolic Content (Tpc) Antioxidant Activity and Antira...mentioning
confidence: 57%
“…The last step for the sample optimization protocol was the pH evaluation in aqueous solvent mixtures. Carob is considered an acidic product, with a pH value close to 6.5, while the pH value of both tested products also ranged between 4.4 and 5.5 [ 32 , 33 ]. Thus, it was an interesting point to investigate, whereas pH adjustment of solvent mixtures would affect metabolites extraction of the acidic matrices.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in enrichment of food qualities of these cones, as well as consumers higher satisfaction. And the high advantages of the molasses that was presented in numerous publications, were highlighted in a new study of Toufeili I, et al [218] from Lebanon. The compared the nutritional qualities of Carob syrup with those of Date and Apple and found that Carob syrup had higher health benefi ts.…”
Section: Discussionmentioning
confidence: 98%